Strategies of Self-Organization and their Relation to the Motivation of Academic Achievement among Students of the Faculty of Educational Sciences at the University of Jordan - Shehada, Fawaz; Alsyouf, Ahmad; Qawasmeh, Rasha (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the strategies of self-regulation and their relation to the motivation of the academic achievement of the students of the Faculty of Educational Sciences at the University of Jordan in light of the gender variables. The study revealed the following results: Strategies for self-regulation among ESF students were high with a mean of 2.72 and a standard deviation of 2.56 There were no statistically significant differences at the level of significance (α = 0.05) due to any gender variables or level of study or specialization in the students in the strategies of self-organization, while the results of the study to the existence of differences of statistical significance at the level of significance (α = 0.05) The degree of self-regulation strategies is only due to the cumulative average. The results of the study also showed that the motivation of students to academic achievement was average with an average of 2.2596 and a standard deviation of 2.8545. The results of the study showed that there is a positive relationship between the strategies of self-regulation and the motivation of the students to achieve the academic achievement at (0.01αα) while the total degree of self-organization strategies and the total degree of motivation of students for academic achievement, with correlation coefficient (347 **).